2013
DOI: 10.1016/j.joep.2013.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Third-party sanctioning and compensation behavior: Findings from the ultimatum game

Abstract: We measured the beliefs and behavior of third parties who were given the opportunity to add to or deduct from the payoffs of individuals who engaged in an economic bargaining game under different social contexts. Third parties rewarded bargaining outcomes that were equal and compensated victims of unfair bargaining outcomes rather than punishing perpetrators, but were willing to punish when compensation was not an available option. Beliefs of whether unequal bargaining outcomes were fair differed based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(85 citation statements)
references
References 26 publications
9
73
0
3
Order By: Relevance
“…We also expanded on the findings of previous researchers and contributed to the literature on the relationship between cooperation and the mechanism of punishment. Our findings are consistent with those of previous studies in which researchers have reported that second and third parties punish individuals who undermine the social norm (e.g., Chavez & Bicchieri, 2013;Fehr & Fischbacher, 2004).…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…We also expanded on the findings of previous researchers and contributed to the literature on the relationship between cooperation and the mechanism of punishment. Our findings are consistent with those of previous studies in which researchers have reported that second and third parties punish individuals who undermine the social norm (e.g., Chavez & Bicchieri, 2013;Fehr & Fischbacher, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…However, there are limitations in second-party punishment, because it is often difficult to achieve cooperation by relying solely on a bilateral mechanism, or through willingness to pay a high cost. Thus, scholars have increasingly focused on punishment from third parties (Chavez & Bicchieri, 2013). Therefore, we proposed the following hypothesis: Hypothesis 2: In comparison with second-party punishment, third-party punishment will involve a reduction in the punishment cost.…”
Section: Second-party Punishmentmentioning
confidence: 99%
See 2 more Smart Citations
“…A common response from both victims and third parties is to punish transgressors for their wrongdoing (Darley & Pittman, 2003;Fehr & G€ achter, 2002;Van Prooijen, 2010;Vidmar, 2000;Wenzel & Okimoto, 2016), because punishment is thought to address both dimensions of symbolic concerns. Nevertheless, victims and third parties alike derive satisfaction from seeing transgressors "get what they deserve" (Chavez & Bicchieri, 2013;Lerner & Miller, 1978). Punishment can also directly elevate the victim's status/power by affirming that the victim is valued (Okimoto & Wenzel, 2011).…”
Section: How Punishment Addresses Symbolic Justice Concernsmentioning
confidence: 99%